The practice of performance management in the Limpopo provincial legislature - Mabelane, Mapoko Jaffreys (My University, 2007)
Refer to the document
Thesis (MPA.) -- University of Limpopo, 2007
Keywords: Performance management; Employees performance; Employees -- Rating of; Performance standards